Environmental Communication Based on Local Wisdom: An Ethnographic Study of the Lubuk Larangan Tradition in Tanjung Belit Village, Indonesia - Dimas Cahya Wiguna; Vani Dias Adiprabowo (Universitas Multimedia Nusantara, 2025)
This research examines environmental communication strategies based on local wisdom, focusing on the Lubuk Larangan tradition in Tanjung Belit Village, Riau Province. In the context of global ecological crises, such as water quality degradation, pollution, and climate change, it is essential to explore how local communities have safeguarded their ecosystems. Lubuk Larangan is a tradition that prohibits fishing in certain areas during specific periods, which serves as a conservation practice and as a means of environmental communication that educates the community about the importance of maintaining the balance of nature. The research method used is qualitative with an ethnographic approach, which allows researchers to explore the social and cultural interactions of the community in maintaining this tradition. The results showed that Lubuk Larangan serves as a symbol of cultural identity, supports social ties, and builds collective awareness of the importance of environmental sustainability. Despite modernization and economic pressures, participatory communication and traditional rituals have proven effective in preserving local wisdom. This research provides valuable insights for developing cultural preservation strategies and raising awareness of local traditions' role in maintaining a sustainable environment.